Application of laser Raman micro-analyses to Earth and planetary materials - Chou, I-Ming; Wang, Alian (Journal of Asian earth sciences, 2017)
[Display omitted] Raman spectroscopy contributed greatly in the past 30years or so for the advances of our understanding of Earth and planetary materials and their associated geological processes. After a brief introduction of the history and basic theory of Raman spectroscopy, the advantages and disadvantages of this spectroscopic analysis method were listed, and examples were given when appropriate. For its applications to the analyses of Earth materials, which include minerals and organic materials, silicate glasses and melts, aqueous solutions, and gases and H2O-gas systems, previous works were discussed and cited. This was followed by a review on “Applications of Raman spectroscopic studies of minerals and fluids to petrogenesis and crustal evolution”, in which several P-T diagrams were given to show metamorphic evolution of ultra-high pressure units, as well as a schematic cross section of the Earth’s outer shells showing recycling of crustal materials in different tectonic regimes. For its applications to the analyses of planetary materials, which include lunar samples, Martian meteorites and other extraterrestrial materials, a brief history on the starting and development of Raman spectroscopy technique was given. We then discussed Raman “point-counting” and “quantitative chemical analysis” methods developed for obtaining quantitative information on mineral proportions and mineral chemistry in planetary surface explorations, respectively. Finally, new developments and future works, which include quantitative analyses, Raman mapping, portable Raman systems, and Raman effects (Resonance Raman Spectroscopy, CARS, SERS), and their associated applications, were discussed.